Aplikasi 3D Mapping Menggunakan Virtual Reality (Studi Kasus Museum Sang Nila Utama) - Efendi, Yoyon; Junaidi, Junaidi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2018)
Museum Sang Nila Utama is a cultural museum which has 3,819 collections covering geology, biology, ethnography, archeology, historica, numism, philology, ceramics, art and technologics. This museum as one of the cultural center and tourism of Riau Malay. Visitors are usually from schools and local tourists. Current museum visits are declining, leading to a lack of museum services and yet no creative strategies to improve it. Plus the thought that the museum is ancient, boring and unkempt. To handle the problem, it needs promotion media in the form of creative media based on technology. Besides, there is still a lack of promotion media in the introduction of museum cultural objects. One of the needs of interactive media applications and technology-based promotions. Applications as a Mobile-based promotional media with Virtual Reality 3D objects tailored to the museum with various collections. This application uses research methods during the modeling process, VR, Mobile and users. This application is modeled using Blender and then processed its VR using Unity Engine. By making the Museum as one of tourist destination and culture of Riau Riau will bring many regional and foreign tourists. It is also to promote the calendar of Riau Province with the tagline "Riau Menyapa Dunia". With various destinations with various bases ranging from culture, history, religion and culinary typical of Riau